Integrated Financial Reporting and Cost Management System - Mohd Waliuddin, Mohd Razali; Suzila, Mohamed Yusof (Unimas, 2017)
Most of accounting information system is focusing on the financial reportingsystem(e.g. Income Statement and Statement of Financial Position). However,the system is limited to specific stakeholders. Managers tend to reduce operatingexpenditure in order to improve net profit rather than cost efficiency. Manyorganizations are not using full potential of cost management due to lessretrieved cost information. Some of the organizations manually obtain theinformation which leads more time and more skilled worker to be hired. This proposed model enables accountants to record financial informationtogether with the cost driver (machine hours, unit output, etc.);and classification(fixed cost,variables, special). Eventually, it can convert to cost information suchas cost of technology infrastructure, activity tasks, project cost, vendor cost,employee cost information, etc. This will speed up the process to obtain costinformation for decision making by management.